Acceptability Of Red Bean-Based Filter Porridge (Phaseolus Vulgaris L) In Patients With Oral Diet Via RSUD Undata Province Central Sulawesi - Yessi Irvina Tombokan; Sri Rezeki Pettalolo; Nurdina, Nurdina (Jurnal EduHealth, 2024)
One way to improve the quality of filter food and prevent the amount of food waste in patients receiving a filter food diet is to modify the menu so that the filter food still has nutrients that meet the patient's needs and has a taste, aroma, and texture that can increase the patient's appetite. The type of food that can be modified in the filter food menu is the use of red beans which have nutrients that are rich in vitamins, minerals and bioactive compounds. Objective: to determine the acceptability of red bean-based filter porridge (Phaseolus Vulgaris L) to patients with oral diet at RSUD Undata, Central Sulawesi Province. This study used a quasi-experimental design. The data collection technique used an acceptability questionnaire. Data analysis included univariate and bivariate using one sample Kolmogorov Smirnov test. Based on the results of bivariate analysis using the one sample Kolmogorov Smirnov test, the results of the acceptability of aroma, color, texture, and taste were obtained with a value of p = 0.000, which means that there is an effect of the acceptability of red bean-based filter porridge (PhaseolusVulgaris L) on the acceptability of taste, aroma, texture, and color of patients with oral diet at RSUD Undata, Central Sulawesi Province. Conclusion: The acceptability of red bean (PhaseolusVulgaris L) based filter porridge has good taste, aroma, texture, and color acceptability.It is expected that further research to analyze the nutrient levels of carbohydrates, protein and fat as well as calories in red bean-based filter porridge and use comparison samples on the acceptability of red bean-based filter porridge with hospital formulated filter porridge.